Estrategias de Afrontamiento Empleadas Por un Grupo de Mujeres Víctimas de Violencia Conyugal (2016)
This research aims to analyze coping strategies employing a group of women victims of domestic violence. The project is approached from the cognitive approach. Using a quantitative methodology which is to study the stability of the couple (despite, or because of) domestic violence, so then starts to understand that while it is true that the emotional dependency is described as behavior addictive to the couple, it is recognized that the dependent person access one way or another to be assaulted by her partner.